2024
DOI: 10.3390/jmse12030391
|View full text |Cite
|
Sign up to set email alerts
|

Transient Tests for Checking the Trieste Subsea Pipeline: Diving into Fault Detection

Silvia Meniconi,
Bruno Brunone,
Lorenzo Tirello
et al.

Abstract: Fault detection in subsea pipelines is a difficult problem for several reasons, and one of the most important is the inaccessibility of the system. This criticality can be overcome by using transient test-based techniques. Such an approach is based on the execution of safe transients that result in small over pressures (i.e., on the order of a few meters of water column). In our companion paper, the procedure involving the transient tests was described in detail. This paper analyses the results of the field te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, the planned steps ensure that the TTBTs are viable within the operational realities of SP management. The companion paper [48] describes the results of the fault detection procedure in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the planned steps ensure that the TTBTs are viable within the operational realities of SP management. The companion paper [48] describes the results of the fault detection procedure in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Once steady-state conditions are established, it is quickly (τ SDV ≃ 0.3 s) and fully closed in step #5. As discussed in detail in the companion paper [48], this maneuver ensures the generation of a small and then absolutely safe pressure wave.…”
Section: Field Procedures Breakdownmentioning
confidence: 99%
“…Over more than half a century of development, both the technology and theory of acoustic emission have significantly improved and found extensive applications in various industries, such as civil engineering, petrochemicals, aerospace, and marine engineering [25][26][27][28][29][30][31], indicating a promising future. Meniconi, S et al [32,33] innovatively proposed a transient analysis method for fault diagnosis of underwater pipelines, which holds significant implications for the advancement of SHM techniques. Grabec I [34] simulated burst-type and continuous-type acoustic emission signals through experiments on aluminum strips and suggested that time delay estimation using the correlation method is feasible, laying the groundwork for subsequent applications of acoustic emission in pipeline leak detection.…”
Section: Introductionmentioning
confidence: 99%
“…The floatation of the pipeline will destroy the overall stability and ultimately affect the safety of the pipelines. The floatation capacity of seabed pipelines has long been considered a key risk element, and studying pipeline floatation is crucial for the checking procedures of subsea pipelines [1,2]. Therefore, to ensure seabed pipeline safety, it is essential to assess the dynamic reaction of the seabed pipeline to combined wave and current loadings, particularly when the pipeline floats.…”
Section: Introductionmentioning
confidence: 99%